Incidence and Predictors of Atrial Fibrillation Progression. Issue 20 (15th October 2019) - Blum, Steffen; Aeschbacher, Stefanie; Meyre, Pascal; Zwimpfer, Leon; Reichlin, Tobias; Beer, Jürg H.; Ammann, Peter; Auricchio, Angelo; Kobza, Richard; Erne, Paul; Moschovitis, Giorgio; Di Valentino, Marcello; et al.
Abstract : Background: The incidence and predictors of atrial fibrillation (AF) progression are currently not well defined, and clinical AF progression partly overlaps with rhythm control interventions (RCIs). Methods and Results: We assessed AF type and intercurrent RCIs during yearly follow‐ups in 2869 prospectively followed patients with paroxysmal or persistent AF. Clinical AF progression was defined as progression from paroxysmal to nonparoxysmal or from persistent to permanent AF. An RCI was defined as pulmonary vein isolation, electrical cardioversion, or new treatment with amiodarone. During a median follow‐up of 3 years, the incidence of clinical AF progression was 5.2 per 100 patient‐years, and 10.9 per 100 patient‐years for any RCI. Significant predictors for AF progression were body mass index (hazard ratio [HR], 1.03; 95% CI, 1.01–1.05), heart rate (HR per 5 beats/min increase, 1.05; 95% CI, 1.02–1.08), age (HR per 5‐year increase 1.19; 95% CI, 1.13–1.27), systolic blood pressure (HR per 5 mm Hg increase, 1.03; 95% CI, 1.00–1.05), history of hyperthyroidism (HR, 1.71; 95% CI, 1.16–2.52), stroke (HR, 1.50; 95% CI, 1.19–1.88), and heart failure (HR, 1.69; 95% CI, 1.34–2.13). Regular physical activity (HR, 0.80; 95% CI, 0.66–0.98) and previous pulmonary vein isolation (HR, 0.69; 95% CI, 0.53–0.90) showed an inverse association. Significant predictive factors for RCIs were physical activity (HR, 1.42; 95% CI, 1.20–1.68), AF‐related symptoms (HR, 1.84; 95% CI, 1.47–2.30), age (HR per 5‐year increase, 0.88; 95% CI, 0.85–0.92), and paroxysmal AF (HR, 0.61; 95% CI, 0.51–0.73). Conclusions: Cardiovascular risk factors and comorbidities were key predictors of clinical AF progression. A healthy lifestyle may therefore reduce the risk of AF progression.